The masquerading presentation of a systemic anaplastic large cell lymphoma, ALK positive: a case report and review of the literature. Issue 6 (2nd November 2017) - Al-Ahmad, Selma; Maertens, Vincent; Libeer, Christophe; Schelfhout, Vera; Vanhoenacker, Filip; Boeckx, Nancy; Vandevenne, Marleen
Abstract : We report an unusual case of systemic anaplastic large cell lymphoma (ALCL), ALK positive with leukemic involvement in a 57-year-old woman. The patient presented with a fulminant respiratory infection unresponsive to treatment requiring intensive care and ventilatory support. The CT scan demonstrated mediastinal and bilateral lymphadenopathy. On peripheral smear a few atypical lymphocytes were visualized. Based on the increasing number of atypical lymphocytes in the daily peripheral bloodsmears, the diagnosis ALCL was suggested. Definitive diagnosis was made on a bone marrow biopsy, with lymphocytes being immunoreactive for CD30, EMA, and ALK. Leukemic peripheral blood involvement in ALCL is an uncommon clinicopathologic entity with unfavorable prognosis. The case we present is perhaps unusual in that a complete respons was achieved, highlighting the importance of prompt diagnosis and judicious management.